Soil organic matter dynamics after addition of nitrogen15 labeled leucaena and dactyladenia residues - Vanlauwe, Bernard; Sanginga, N.; Merckx, Roel (Wiley, 1998)
Quantification of the movement of residue N through various biologically meaningful soil organic matter (SOM) fractions is essential in low-input tropical cropping systems for the development of management practices aimed at optimizing N-use efficiency. The flow of N derived from 15N-labeled leucaena [Leucaena leucocephala (Lam.) de Wit] and dactyladenia [Dactyladenia barteri (Hook f ex Oliv.) Engl.] leaf residues was followed through the SOM of different particle-size fractions during 858 d. A bioassay study with maize (Zea mays L.) was carried out to assess the availability of residue-derived N (RDN) incorporated in the particle-size fractions. At 53 d after residue application (DAA), most of the RDN was found in the fraction between 0.250 and 2 mm (O250) in the leucaena treatment and in the fraction >2 mm and the surface litter (O2000 + SL) in the dactyladenia treatment. The RDN content of all fractions <0.250 mm was significantly higher in the leucaena than in the dactyladenia treatment up to 471 DAA. The proportion of the total amount of RDN recovered in the fractions <2 mm shifted toward the smaller particle-size classes near the end of the experiment. Highly significant (P < 0.001) relationships between RDN present in the particulate organic matter (POM) and uptake of RDN by maize indicated the relatively high availability of RDN in the POM. Fractionating the SOM pool into different particle-size classes yielded useful information on the relative contributions of the different SOM fractions to N turnover and availability. This information is needed in identifying SOM pools with direct relevance to plant nutrition in low-input cropping systems.